Enhancing Skin Delivery and Stability of Vanillic and Ferulic Acids in Aqueous Enzymatically Extracted Glutinous Rice Husk by Nanostructured Lipid Carriers - Sudarat Jiamphun; Wantida Chaiyana (MDPI AG, 2023)
The present study aimed to develop nanostructured lipid carriers (NLCs) and evaluate their effectiveness in enhancing the delivery and stability of vanillic and ferulic acid in the aqueous enzymatic extract of glutinous rice husk using a 0.5% w/w cellulase solution (CE0.5). NLCs were developed using a high-pressure homogenization technique and characterized for their particle size, polydispersity index, and zeta potential. The entrapment efficiency, physical and chemical stability, release profile, skin permeation, and skin retention of the NLCs loaded with CE0.5 were evaluated. It was observed that NLCs with high entrapment efficiencies efficiently encapsulate and protect both vanillic and ferulic acid, in contrast to a solution. The controlled and sustained release profile of vanillic acid and ferulic acid from NLCs suggests their potential for prolonged and targeted delivery. The findings also demonstrate the superior skin retention capabilities of NLCs without permeation compared to the solution. Notably, NLC2 exhibited the highest delivery into the skin layer, which can be attributed to its smaller particle size (107.3 ± 1.3 nm), enabling enhanced skin penetration. This research highlights the promising application of NLCs in enhancing the delivery and stability of bioactive compounds in cosmetic formulations and related fields.